(untitled) (Sociologisk Forskning, 2009)
The issues of gender equality and women’s human rights have become major spheres of academic debate, policy and activism in virtually every corner of the globe. Violence against women, a relative latecomer to the international gender agenda, has provided a particularly critical entry point in challenging long standing gender ideologies and taboos as well as the gender biased mainstream human rights framework that kept, until recently, the gender specific abuses women experience outside of public scrutiny.